Cryptic domains of tenascin-C differentially control fibronectin fibrillogenesis. - To, W; Midwood, K (2010)
The three-dimensional organization of the ubiquitous extracellular matrix glycoprotein fibronectin regulates cell fate and morphogenesis during development; in particular tubule formation that constitutes the vasculature, lung and kidney. Tenascin-C is a matrix protein with a restricted expression pattern; it is specifically up-regulated at sites of fibronectin fibril assembly during development and in remodeling adult tissues. Here we demonstrate that specific domains of tenascin-C inhibit fibronectin matrix assembly whereas full-length tenascin-C does not. These domains act via distinct mechanisms: TNfn1-8 blocks fibrillogenesis by binding to fibronectin fibrils and preventing intermolecular fibronectin interactions whilst FBG acts independently of binding to fibronectin and instead is internalized and causes cytoskeletal re-organization. We also show that TNfn1-8 disrupts epithelial cell tubulogenesis. Our data demonstrate that tenascin-C contains cryptic sites which can control tissue levels of fibrillar fibronectin either by preventing de novo fibril assembly or reducing levels of deposited fibronectin. Exposure of these domains during tissue remodeling may provide a novel means of controlling fibronectin assembly and tubulogenic processes dependent on the assembly of this matrix.